THE ENGLISH / ARABIC TRANSLATION METHODS OF METAPHORS AND IDIOMS: SPEECHES OF KING ABDULLAH II - Bayan Ibrahim Mutleq Al-kaabneh; Ahmad Taufik Hidayah Abdullah, (INTERNATIONAL JOURNAL OF HUMANITIES, PHILOSOPHY AND LANGUAGES (IJHPL), 2024)
Translation is a process of transferring meanings from a source language into a target language. Translators often state that figurative language like metaphor and idiom present challenges in the translation process.Metaphors and idioms play a central role in political discourse; they are used for rhetorical persuasive purposes This research aims at finding the translation methods provided by the Royal Court translators when translating metaphors and idioms in the political speeches of king Abdullah II of Jordan from English into Arabic. In the present study, Vinay and Darbelnet (1995) theory of translation methods is adapted in order to achieve the objectives of the study. Vinay and Darbelnet (1995) classify the translation methods into calque, borrowing, literal, equivalence, modulation, adaptation, and transposition. This study deploys qualitative method in analyzing metaphors and idioms in the speeches of king Abdullah II. The main data for this research are the speeches and discussion papers of his majesty King Abdullah II which are published in his official website: (http://www.kingabdullah.jo) . The findings of the study revealed that translators of the royal court apply Vinay and Darbelnet translation methods (1995) in translating both metaphors and idioms. namely, borrowing, claque, literal, transportation, modulation, equivalence, and adaptation.